Complex‐mediated nucleophilic aromatic substitution with aryl nitriles to realize intramolecular flapping‐restricted D‐A AIEgens for bioimaging - Feng Liu; Junkai Liu; Junyi Gong; Runfeng Lin; Siyuan Qiu; Zicheng Liu; Chongyang Li; Miao Meng; Shijie Li; Mei Tu; Jacky W. Y. Lam; Guangle Niu; et al. (Smart Molecules, 2025)
Abstract Donor‐acceptor (D‐A) compounds are particularly important in optoelectronic and biological applications. However, they are normally synthesized in the presence of transition metal catalysts. Herein, we report a metal‐free method by a complex‐mediated nucleophilic aromatic substitution of aryl nitriles with amines. The method can lead to rich D‐A type aggregation‐induced emission luminogens (AIEgens) with tunable properties. They emit from deep‐blue to yellow‐green and possess high photoluminescence quantum yields up to 70.5% in the aggregate state. Interestingly, the suppression of intramolecular flapping is proved to play an indispensable role in the AIE behavior, which is different from the mechanism met in other AIEgens. Moreover, the biocompatible AIEgens possess specific staining of lipid droplets in HeLa cells and the superiority of identifying fatty liver over traditional Oil Red O staining is exhibited.